Study of qualitative properties of groundwater and its suitability for different uses in the Eastern of the Al- Dour city/ Salahaldin/ Iraq - Ehab Mohammad A; Ektifa Taha A; Fatma Adnan S; Rania Haithem S (Tikrit Journal of Pure Science, 2020)
A study was conducted to evaluate the groundwater in Abo- Dalaf Area, far east of  Al-Dour city, Salahaldin governorate. The field work included, field visits to the area to know the geological reality and to identify the most important geomorphological and structural phenomena, then 10 wells were selected, distributed over the study area.